Unilateral Hemiparesis with Thoracic Epidural in an Adolescent - Rosalie F. Tassone; Christian Seefelder; Navil F. Sethna (Case Reports in Anesthesiology)
Objective. Unilateral sensory and motor blockade is known to occur with epidural anesthesia but is rarely reported in children. The differential diagnosis should include the presence of a midline epidural septum. Case Report. We describe a case of a 16-year-old adolescent who developed repeated complete unilateral extensive epidural sensory and motor blockade with Horner’s syndrome after thoracic epidural catheter placement. This unusual presentation of complete hemibody neural blockade has not been reported in the pediatric population. Maneuvers to improve contralateral uniform neural blockade were unsuccessful. An epidurogram was performed to ascertain the correct location of the catheter within the epidural space and presence of sagittal compartmentalization. Conclusion. This case report highlights a less frequently reported reason for unilateral sensory and motor blockade with epidural anesthesia in children. The presence of a midline epidural septum should be considered in the differential diagnosis of unilateral epidural blockade.